ORIENTASI PASAR, STRATEGI DIFERENSIASI, DAN INOVASI PRODUK TERHADAP KEUNGGULAN BERSAING BERPENGARUH PADA INDUSTRI ENDEK - Nugraha, Nyoman Agus Surya; Sukaatmadja, I Putu Gde (E-Jurnal Manajemen; Vol 9 No 8 (2020), 2020)
This research conducted in Klungkung with 96 owners of the endek fabric business as samples. Determination of samples by Saturated Sampling. Data collection through questionnaires and analyzed with multiple linear regression. Based on the results, Market Orientation, Differentiation Strategy, and Product Innovation simultaneously have significant effect on Competitive Advantage. There is a partially positive and significant influence between Market Orientation and Competitive Advantage in the Endek Industry. There is a positive and partially significant influence between the Differentiation Strategy on Competitive Advantage in the Endek Industry. There is a partially positive and significant influence between Product Innovation on Competitive Advantage in the Endek Industry. Efforts to increase the competitive advantage of the endek industry can be carried out by endek entrepreneurs by collecting information about customer needs, making endek fabric designs that are different and easily recognizable compared to competitors' products and trying to sell products abroad. Keywords: market orientation, differentiation strategy, product innovation, competitive advantage.